2021
DOI: 10.3390/jcm10061227
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Patellar Resurfacing in TKA: A Combined Analysis of Registry Data and Biomechanical Testing

Abstract: The German Arthroplasty registry (EPRD) has shown that different prosthesis systems have different rates of secondary patellar resurfacing: four years after implantation, the posterior-stabilized (PS) Vega prosthesis has a 3.2% risk of secondary patellar resurfacing compared to the cruciate-retaining (CR) Columbus prosthesis at 1.0% (both Aesculap AG, Tuttlingen, Germany). We hypothesized that PS implants have increased retropatellar pressure and a decreased retropatellar contact area compared to a CR design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…However, these cadaver studies did not control for the effect of component malalignment on PF contact. On the other hand, Bauer et al reported no differences in retropatellar contact pressure between PS and CR knees, but the patellae were not resurfaced, and external loads were low (50 N) 20 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, these cadaver studies did not control for the effect of component malalignment on PF contact. On the other hand, Bauer et al reported no differences in retropatellar contact pressure between PS and CR knees, but the patellae were not resurfaced, and external loads were low (50 N) 20 .…”
Section: Discussionmentioning
confidence: 97%
“…Most of the previous studies evaluating PF contact status were conducted in cadaveric knees 6 , 7 , 9 , 11 , 12 , 16 . However, it is technically challenging to apply large loads equivalent to multiples of body weights in cadaver experiments which tends to underestimate PF pressures 20 . In addition, surgical variations in bone cuts and inter-individual differences in bony anatomy and soft tissues tend to confound the analysis of PF contact.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of clinical practices have shown that, due to the changes in the existing mechanical properties and mucosa of the joint interface after TKA, the patella has lost its original motion performance. [ 17 ] If the patella is not replaced, it may cause wear of the patella and femoral implants, leading to adverse consequences. [ 17 ] Serious cartilage erosion is often found in the second operation.…”
Section: Discussionmentioning
confidence: 99%
“…The established Munich knee rig, which has six degrees of freedom, performed an active movement of 30-130° of flexion in the knee joint at a speed of 3°/s [13][14][15][16][17][18]. The experimental setup does not allow movement at 0° flexion due to the uncontrolled hamstring muscles which normally induce the flexion movement.…”
Section: Methodsmentioning
confidence: 99%
“…The fibula head was fixed to the tibia with a cortical screw to ensure stability during the test-setup. The ends of the tibia and femur were embedded into metal cups using epoxy resin to clamp the knee joint into the knee rig [13][14][15][16][17][18]. To secure a malalignment of the femoral bone within the metal cups, the internal/ external rotation of the posterior condyles of the femur were aligned parallel to the hip flexion axis of the experimental setup in the transversal plane.…”
Section: Human Specimen and Implantationmentioning
confidence: 99%